2017
DOI: 10.1111/febs.14282
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded protein exhibits antiassociation activity toward the 50S subunit facilitating 70S ribosome dissociation

Abstract: The ability of the ribosome to assist in the folding of proteins both in vitro and in vivo is well documented. The interaction of an unfolded protein with the peptidyltransferase center of the bacterial large ribosomal subunit is followed by release of the protein in a folding-competent state and rapid dissociation of ribosome into its subunits. Our studies demonstrate that the 50S subunit-associated antiassociation ability of an unfolded protein might contribute significantly to its ability to mediate energy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 49 publications
(95 reference statements)
1
13
0
Order By: Relevance
“…Our earlier ex‐vivo studies performed using E . coli cell lysate had demonstrated that, the isolated ribosomal subunits formed due to the unfolded protein‐mediated 70S Ec ‐free dissociation, increased the susceptibility of the ribosome towards degradation by cellular ribonucleases [19]. In the present study, similar assays were performed in which 0.1 µ m 70S Ec was incubated with a 10‐fold stoichiometric excess of HPF and YfiA in the presence of 0.5 µ m uBCAII.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Our earlier ex‐vivo studies performed using E . coli cell lysate had demonstrated that, the isolated ribosomal subunits formed due to the unfolded protein‐mediated 70S Ec ‐free dissociation, increased the susceptibility of the ribosome towards degradation by cellular ribonucleases [19]. In the present study, similar assays were performed in which 0.1 µ m 70S Ec was incubated with a 10‐fold stoichiometric excess of HPF and YfiA in the presence of 0.5 µ m uBCAII.…”
Section: Resultsmentioning
confidence: 76%
“…It might be argued that the inability of the unfolded protein to associate with the HPF or YfiA bound 70S Ec ribosome could have prevented the initiation of ribosome splitting. In our earlier studies, the ribosome‐uBCAII complexes were separated from the unassociated protein by ultrafiltration and detected by western blot analysis using anti‐BCAII antibody [19]. Similar experiments were performed to analyse whether uBCAII and the factors HPF and YfiA could simultaneously bind to the ribosome under our experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental investigation of RNA binding to the GST-FXIIIA fusion protein is beyond the scope of the current project, and instead the following speculation may be offered. It is well known that unfolded proteins bind to the 50S subunit of the prokaryotic ribosome, and in a recent report, Pathak et al (119) demonstrated that the presence of an unfolded protein in above stoichiometric amounts, promotes dissociation of ribosome subunits, thereby reducing the fold-assisting function of the ribosome. As suggested above, at the relatively high incubation temperature, the FXIIIA polypeptide is assembled faster than it folds into the native conformation.…”
Section: Discussionmentioning
confidence: 99%
“…This unfolded FXIIIA may thus have caused the dissociation of E. coli ribosomes. Such dissociated ribosomes are susceptible to degradation by cellular ribonucleases (119). Whether the actual ribosome degradation has or has not taken place in the initial 'IPTG expression' efforts, it is possible that some ribosomal RNA remained bound with the fusion protein on the column despite excessive washing steps.…”
Section: Discussionmentioning
confidence: 99%